Memories of a Bygone Age : Qajar Persia and Imperial Russia 1853-1902 - Arfaʻ, Riz̤ā, 1850 or 1851-1937 or 1938 (Gingko Library, 2016)
"Set against the backdrop of Iran's struggle against the rising powers of Russia and Britain, the memoirs of Mirza Riza Khan Arfa'-ed-Dowleh--otherwise known as Prince Arfa (1853-1902)--are packed with picaresque adventures as the prince tells the story of his rise from humble provincial beginnings to the heights of the Iranian state. With this translation, his incredible story is brought to life for the first time in English. Prince Arfa writes with arresting wit about the deadly intrigues of the Qajar court. Lamentingly, but resolutely, he chronicles the decline of Iran from a once great empire to an almost bankrupt, lawless state, in which social unrest is channelled and exploited by the clergy. He describes the complex interactions between Iran and Europe, including an account of Naser-od-Din Shah's profligate visits to Britain and France; the splendor and eccentricities of the doomed Tsar Nicholas II's court; the Tsar's omen-laden coronation; and his own favor with the Tsarina, who would grant him concessions on matters of vital importance to his country. The result is a memoir of extraordinary political intrigue."--Publishers